Enhancing Performance of Porous Si-Doped GaN based MSM Photodetector Using AC Technique - Mahmood, Ainorkhilah; Hassan, Zainuriah; Rahim, Alhan Farhanah Abd; Radzali, Rosfariza; Ahmed, Naser M. (2017)
In this work, we report the formation of porous Si-doped GaN films under a novel alternating current (sine-wave a.c. (50 Hz)) photo-assisted electrochemical etching (ACPEC) conditions. The formation of porous Si-doped GaN by the novel ACPEC is performed in the same electrolyte concentration (4% KOH) used in common de constant current electrochemical etching process. Ultra-violet (UV) illumination is used to assist in the generation of electron-hole pairs, where etching proceeds through the oxidation and consequently, dissolution of the semiconductor surface. The ac formed porous Si-doped GaN with excellent structural and optical properties. According to the FESEM micrographs, the GaN thin films exhibit a homogeneous nanoporous structures with spatial nano-flakes arrangement. The porous layer exhibited a substantial photoluminescence (PL) intensity enhancement with red-shifted band-edge PL peaks associated with the relaxation of compressive stress. The shift of E2(high) to the lower frequency in Raman spectra of the porous GaN films further confirms such a stress relaxation. Electrical characterizations of the MSM photodiodes were carried out by using current-voltage (1-V) measurements indicated that the devices were highly sensitive to ambient light.